2013
DOI: 10.1159/000353256
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Automatic Triggering and Cycling System on Comfort and Patient-Ventilator Synchrony during Pressure Support Ventilation

Abstract: Background: The digital Auto-Trak™ system is a technology capable of automatically adjusting the triggering and cycling mechanisms during pressure support ventilation (PSV). Objective: To compare Auto-Trak with conventional settings in terms of patient-ventilator synchrony and discomfort. Methods: Twelve healthy volunteers underwent PSV via the mouth by breathing through an endotracheal tube. In the conventional setting, a pressure support of 8 cm H2O with flow cycling (25% peak inspiratory flow) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 20 publications
(29 reference statements)
1
14
0
1
Order By: Relevance
“…In a previous study conducted by our research group, Auto-Trak and manual adjustments of the cyclingoff criteria showed similar results with respect to patientventilator synchrony and patient comfort. 23 In the present study, the use of Auto-Trak in a single-limb circuit ventilator showed similar results to conventional settings concerning cycling asynchrony.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In a previous study conducted by our research group, Auto-Trak and manual adjustments of the cyclingoff criteria showed similar results with respect to patientventilator synchrony and patient comfort. 23 In the present study, the use of Auto-Trak in a single-limb circuit ventilator showed similar results to conventional settings concerning cycling asynchrony.…”
Section: Discussionsupporting
confidence: 74%
“…The Auto-Trak system consists of a technology capable of automatically adjusting, breath by breath, the triggering and cycling mechanisms. 23 Table 2 shows the configuration of the rise time and the inspiratory trigger sensitivity, which was set to the minimum value on all ventilators to prevent the occurrence of auto-triggering. 15…”
Section: What This Paper Contributes To Our Knowledgementioning
confidence: 99%
“…Patient-ventilator asynchrony can be defi ned as a mismatch between the patient, regarding time, fl ow, volume, or pressure demands of the patient respiratory system, and the ventilator, which supplies such demands, during MV. (3) Asynchrony events can range from subtle changes, the detection of which demands strong suspicion and refi ned monitoring, to an evident "struggle" between the patient and the ventilator.…”
Section: Defi Nition and Epidemiologymentioning
confidence: 99%
“…In clinical practice, this may have an important influence on the numbers of asynchronous events and/or patient comfort [24].…”
Section: Asynchronymentioning
confidence: 99%